Soybean root growth and yield in rotation with cover crops under chiseling and no-till - Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP] (Elsevier B.V., 2010)
Compacted subsoil layers result in shallow root systems hindering the absorption of water and nutrients by plants. Disruption of soil compacted layers can be promoted by mechanical and/or biological methods, using plants with strong root systems. The immediate and medium term effects of mechanical chiseling and crop rotations on soybean root growth and yield were evaluated during four years in Brazil. Triticale (X Triticosecale Wittmack) and sunflower (Helianthus annuus L) were grown in the autumn-winter (April-August). In the next spring (September-October/early November), designated plots were chiseled down to 0.25 m or planted to millet (Pennisetum glaucum L), sorghum (Sorghum bicolor (L.) Moench) and sunn hemp (Crotalaria juncea L.), grown as cover crops, preceding soybean (Glycine max (L.) Merrill). Chiseling was done only in the first year, and these plots were left fallow during the spring (September-October/early November) for the rest of the experiment. Chiseling resulted in lower soil penetration resistance and higher soybean yields in the first year. However, in the following years soybean root growth in depth was increased under rotation with triticale and pearl millet due to the presence of biopores and a decrease in soil penetration resistance. Soybean yields tended to decrease over the years in plots that were chiseled when compared with plots under crop rotation. Chiseling can be replaced by crop rotations involving species with aggressive root systems in order to alleviate deleterious effects of soil compaction on soybean yields in tropical soils. This effect is gradual, thus crop rotation will be fully effective in remediating soil compaction in a 3- to 4-year term. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Biological subsoiling; Cover crop; Soil compaction; Root growth